Pierre Robin sequence with tetralogy of Fallot: An unusual finding - Javed, Nismat; Malik, Jahanzeb (International Journal of Health Sciences, 2021)
Pierre-Robin sequence has been known to present with multiple somatic abnormalities. It is known that the syndrome impairs cardiogenesis. However, the reason for this is unknown. Impaired cardiogenesis manifests in the form of various defects such as ventricular septal defect and atrial septal defect but presence of tetralogy of Fallot is very rare.